Combining Innovative Bioink and Low Cell Density for the Production of 3D-Bioprinted Cartilage Substitutes: A Pilot Study - Christel Henrionnet; Léa Pourchet; Paul Neybecker; Océane Messaoudi; Pierre Gillet; Damien Loeuille; Didier Mainard; Christophe Marquette; Astrid Pinzano (Hindawi Limited, 2020)
3D bioprinting offers interesting opportunities for 3D tissue printing by providing living cells with appropriate scaffolds with a dedicated structure. Biological advances in bioinks are currently promising for cell encapsulation, particularly that of mesenchymal stem cells (MSCs). We present herein the development of cartilage implants by 3D bioprinting that deliver MSCs encapsulated in an original bioink at low concentration. 3D-bioprinted constructs (10×10×4 mm) were printed using alginate/gelatin/fibrinogen bioink mixed with human bone marrow MSCs. The influence of the bioprinting process and chondrogenic differentiation on MSC metabolism, gene profiles, and extracellular matrix (ECM) production at two different MSC concentrations (1 million or 2 million cells/mL) was assessed on day 28 (D28) by using MTT tests, real-time RT-PCR, and histology and immunohistochemistry, respectively. Then, the effect of the environment (growth factors such as TGF-β1/3 and/or BMP2 and oxygen tension) on chondrogenicity was evaluated at a 1 M cell/mL concentration on D28 and D56 by measuring mitochondrial activity, chondrogenic gene expression, and the quality of cartilaginous matrix synthesis. We confirmed the safety of bioextrusion and gelation at concentrations of 1 million and 2 million MSC/mL in terms of cellular metabolism. The chondrogenic effect of TGF-β1 was verified within the substitute on D28 by measuring chondrogenic gene expression and ECM synthesis (glycosaminoglycans and type II collagen) on D28. The 1 M concentration represented the best compromise. We then evaluated the influence of various environmental factors on the substitutes on D28 (differentiation) and D56 (synthesis). Chondrogenic gene expression was maximal on D28 under the influence of TGF-β1 or TGF-β3 either alone or in combination with BMP-2. Hypoxia suppressed the expression of hypertrophic and osteogenic genes. ECM synthesis was maximal on D56 for both glycosaminoglycans and type II collagen, particularly in the presence of a combination of TGF-β1 and BMP-2. Continuous hypoxia did not influence matrix synthesis but significantly reduced the appearance of microcalcifications within the extracellular matrix. The described strategy is very promising for 3D bioprinting by the bioextrusion of an original bioink containing a low concentration of MSCs followed by the culture of the substitutes in hypoxic conditions under the combined influence of TGF-β1 and BMP-2.